In-Mg-hydrotalcite anionic clay as catalyst or catalyst precursor for friedel-crafts type benzylation reactions - Choudhary, Vasant R.; Jha, Rani; Narkhede, V. S. (Journal of Molecular Catalysis A-Chemical, 2005)
In-Mg-hydrotalcite (Mg/In = 3) anionic clay with or without calcination (at 200-800 degrees C) or HCl pretreatment at different temperatures (26 and 80 degrees C) and periods (0.1 or 1.0 h) has been used for the benzylation of benzene and/or substituted benzenes by benzyl chloride. The hydrotalcite before and after its calcination or HCl pretreatment was characterized for its surface area, crystalline phases and basicity. The hydrotalcite particularly after its use in the benzylation reaction, and the catalyst derived from it by its calcination at 800 degrees C followed by HCl pretreatment (at 80 degrees C for 1.0 h), shows high catalytic activity even for the benzylation of benzene. The catalytically active species present in the catalyst in its most active form are the chlorides and oxides of indium on the catalyst surface. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: activation of In-Mg-hydrotalcite by calcination; activation of In-Mg-hydrotalcite by HCl pretreatment; benzylation of benzene; benzylation of substituted benzenes; In-Mg-hydrotalcite